Adoption and use of ICT for e-Government services: The case of Mozambique - Rhongo, D. L.; Almeida, A. de.; David, N. (2019 IST-Africa Week Conference, IST-Africa, 2019)
The relevance of e-government for the modernisation of public services motivated this study on the Mozambican citizens' attitude towards the use and acceptance of ICTs for e-government. This paper analyses the presence of communication infrastructure in Mozambican villages and the adoption and acceptance of electronic services accessible through computer and mobile devices, considering a sample group of e-learning students of the Catholic University of Mozambique. The results were obtained through a questionnaire, which comprehended the levels of technological usage and acceptance of ICTs and e-services. All the participants have used ICT devices and are aware of its importance. This study suggests that facilitating conditions influence the intention of using e-government, as well as the user's behaviour. The presence of telecommunications network infrastructure in all districts of the country and the device's price value plays an important role for using the technology. Additionally, the study hints at the relationship between various socio-economic factors in Mozambique and the use and acceptance of these technologies, such as gender and literacy, which are relevant to public policies in this domain.